Recruiting racially and ethnically diverse smokers seeking treatment: Lessons learned from a smoking cessation randomized clinical trial. (January 2022) - Asfar, Taghrid; Koru-Sengul, Tulay; Antoni, Michael A.; Dorsey, Asha; Ruano Herreria, Estefania C.; Lee, David J.; Webb Hooper, Monica
Highlights: Improving minorities' recruitment in smoking cessation trials is a high priority. Multiple recruitment strategies were needed to recruit minorities in the trial. Proactive recruitment and flyers were successful among African Americans. Culturally tailored recruitment strategies were crucial to reach Hispanics/Latinxs. Flyer distribution and newspaper ads were the most economic recruitment methods. Abstract: Introduction: Recruiting racial/ethnic minorities in smoking cessation trials is a priority. This study described lessons learned from recruiting a diverse sample of African American, White, and Hispanic/Latinx smokers in a smoking cessation trial. Methods: We implemented a 42-month recruitment campaign utilizing reactive (e.g., word-of-mouth, newspaper, radio, online ads, flyers, community partnerships) and proactive (e.g., direct invitations) strategies. We included 821 participants in the analysis. We described our recruitment strategies' implementation, their enrollment yield and rate (number enrolled/number screened) by race/ethnicity, and direct cost-per-participant (CPP: total cost/number of enrolled) for paid strategies. Results: Enrollment yields were higher using reactive strategies than proactive strategies (94.3% vs. 5.7%). The top source of enrollment was word-of-mouth among African Americans (36%) and Whites (44%), and flyers among Hispanics/Latinxs (34%). Proactive recruitment, word-of-mouth, and flyers were more successful among African Americans than other groups. Newspaper and online ads were more successful among Hispanics/Latinxs than other groups ( P < .05). Word-of-mouth was cost-free and yielded 23.1% of enrollment. The most economic method among paid strategies was flyer distribution (CPP = 47.6; yield 17.5%), followed by newspaper (194.7; 23.7%) and online advertisements (264.6; 24.0%). Radio and television ads were the most expensive and produced the least participant yield (4, 755.6; 0.8%). Conclusion: Recruiting racially/ethnically diverse samples into smoking cessation clinical trials requires implementing multiple strategies and adjusting these strategies based on their enrollment yield and cost. Word-of-mouth, flyers, and newspaper and online ads were more successful among racial/ethnic minorities. Flyers and newspaper ads were the most economic methods for recruitment.